FloodMEMORY - model simulations - Janes, Victoria (Cranfield University, 2017)
Outputs from SHETRAN simulations from FloodMEMORY project. See article "Improving bank erosion modelling at catchment scale by incorporating temporal and spatial variability".
Keywords: SHETRAN'; 'model'; 'sediment'; 'bank erosion'; 'Geomorphology and Regolith and Landscape Evolution'; 'Environmental Science'; 'Hydrology'